Report of a New Pediatric Patient with the SLC1A4 Variant and a Brief Review of the Literature - Yalçın, Hatice Yelda; Cinleti, Tayfun; Yeşilyurt, Ahmet; Aydın, Nihal (Journal of Pediatric Neurology, 2024)
Spastic tetraplegia, thin corpus callosum, and progressive microcephaly (SPATCCM) is an autosomal recessive disorder characterized by the onset of those features and severely impaired global development in early infancy, and caused by biallelic deleterious SLC1A4 variants. SLC1A4 encodes for the neutral amino acid transporter, ASCT1, which is necessary for L-serine and D-serine cellular transport to neurons. The objective of this study was to contribute to the genotype–phenotype correlation of SLC1A4 variants. We evaluated a Turkish patient presenting with SPATCCM without seizures and reviewed all previously reported cases of the SLC1A4 mutation. Whole exome sequencing revealed a missense biallelic p.R457W variant in SLC1A4 in a child of Palestinian origin. We suggest that the SLC1A4 should be considered in the diagnosis of unexplained severe early-onset neurodevelopmental impairment, progressive microcephaly, and spastic tetraparesis with or without epilepsy, regardless of ethnicity and encourage the analysis of SLC1A4 variants via molecular genetic testing. The presence or absence of epilepsy should not distract from the diagnosis.
Keywords: SLC1A4; microcephaly; spasticity; thin corpus callosum; epilepsy